Examination of emotional intelligence in codification of job stress model among physicians: the mediating role of existential anxiety - Maryam Jami; Fatemeh Shahabizadeh (Gonabad University of Medical Sciences, 2018)
Emotional intelligence is the measure of an individual's abilities to recognise and manage their emotions, and the emotions of other people, both individually and in groups. The aim of the present study was to explore the role of emotional intelligence and existential anxiety in codification of job stress model. This research was conducted using correlational method. The statistical population included physicians employed in the hospitals. 240 physicians participated in this research. Three questionnaires; namely, emotional intelligence, existential anxiety, and job stress were prepared and distributed to among the participants. Data analysis was performed using Lisrel statistical software and structural equation modeling. The results showed that emotional intelligence can decrease job stress indirectly through mediating role of existential anxiety reduction. Therefore, strengthening emotional intelligence indicators particularly emotions and optimism, on one hand, and reducing appraisal of emotions ,on the other hand, may result in the decreased existential anxiety and job stress and; consequently, can lead to promotion of physician's performance.